2016
DOI: 10.1016/j.cell.2016.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Coordination of Mitochondrial Stress Signaling and Proteostasis

Abstract: SUMMARY During neurodegenerative disease, the toxic accumulation of aggregates and misfolded proteins is often accompanied with widespread changes in peripheral metabolism, even in cells in which the aggregating protein is not present. The mechanism by which the central nervous system elicits a distal reaction to proteotoxic stress remains unknown. We hypothesized that the endocrine communication of neuronal stress plays a causative role in the changes in mitochondrial homeostasis associated with proteotoxic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
223
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(233 citation statements)
references
References 55 publications
9
223
1
Order By: Relevance
“…Two recent advancements have been made into the identity of the mitokines that regulate the cell non-autonomous control of the UPR mt . In the first study, the bioamine neurotransmitter serotonin was found to be required for activation of the UPR mt in the intestine as a consequence of mitochondrial protein aggregate accumulation in neurons (26). In a parallel study, interneuron secretion of the neuropeptide FLP-2 was necessary and sufficient for UPR mt activation in the intestine (27).…”
Section: Caenorhabditis Elegansmentioning
confidence: 92%
“…Two recent advancements have been made into the identity of the mitokines that regulate the cell non-autonomous control of the UPR mt . In the first study, the bioamine neurotransmitter serotonin was found to be required for activation of the UPR mt in the intestine as a consequence of mitochondrial protein aggregate accumulation in neurons (26). In a parallel study, interneuron secretion of the neuropeptide FLP-2 was necessary and sufficient for UPR mt activation in the intestine (27).…”
Section: Caenorhabditis Elegansmentioning
confidence: 92%
“…Mitochondrial unfolded protein response (UPR mt ) is an evolutionarily conserved system that confers resistance to mitochondrial stresses by upregulating mitochondrion-specific chaperones, such as heat shock protein 6 (HSP-6) or HSP-60 (16,34). To investigate whether loss of asymmetric arginine dimethylation on mitochondrial proteins causes stress in mitochondria, we employed a highly sensitive reporter strain, the zcIS13[Phsp6::gfp] strain, that induces hsp-6 promoter-driven green fluorescent protein (GFP) expression specifically responding to mitochondrial stresses (16,35). As shown in Fig.…”
Section: Prmt-1 Regulates Mitochondrial Functionmentioning
confidence: 99%
“…While the relationship between FLP-2 and serotonin has not been examined, it is safe to assume that a number of interesting signaling events occur downstream of both molecules to affect the regulation of intestinal ATFS-1. Both studies indicate that ATFS-1 is essential in both the sensing neurons as well as in the intestinal cells for non-autonomous UPR mt activa-tion [3,5]. In neurons where mitochondria are perturbed directly, ATFS-1 activation is likely achieved by impaired mitochondrial protein import effi ciency.…”
mentioning
confidence: 99%
“…activation likely promotes coordination of mitochondrial function or metabolic adaptations across tissues, which may contribute to the metabolic abnormalities found in distal tissues in neurodegenerative diseases such as Huntington's disease and Parkinson's disease [3]. Because neurons do not innervate the worm intestine, non-automonous UPR mt signaling has been hypothesized to be mediated by a "mitokine" [4], however, the mode of signal transduction has remained unclear, as have the functional ramifications.…”
mentioning
confidence: 99%
See 1 more Smart Citation